Perioperative variation in serum FGF-23 level and its correlation with MACCE risk in unprotected left main coronary artery disease patients receiving coronary artery bypassing grafting - Wang, Fanshun; Ma, Runhua; Wang, Chunsheng (Frontiers in Surgery, 2022)
Objective: Fibroblast growth factor-23 (FGF-23) mediates vascular endothelial injury, inflammatory infiltration, and atherosclerosis, which could reflect major adverse cardiac and cerebrovascular event (MACCE) risk in several cardiovascular diseases. This study aimed to further investigate the perioperative change of FGF-23, as well as its association with clinical characteristics and MACCE risk in unprotected left main coronary artery disease (ULMCAD) patients receiving coronary artery bypass grafting (CABG). Methods: Totally, 226 ULMCAD patients who underwent CABG were enrolled. Serum samples of the patients were collected on the day before CABG, the third day (D3) after CABG, and at discharge; then the FGF-23 level was determined by enzyme-linked immunosorbent assay. MACCE rate was recorded during a median follow-up of 25.5 (range: 2.0-46.0) months. Results: The median, interquartile range (IQR), and range of FGF-23 level in ULMCAD patients receiving CABG were 717.0, 582.5-869.8, and 407.0-1765.0 pg/mL. FGF-23 level was increased in patients with both previous heart failure (P=0.046) and chronic renal failure (P=0.009) compared to those without. FGF-23 level increased from before surgery (median (IQR): 712.5 (574.5-879.8) pg/mL) to D3 (median (IQR): 844.0 (666.0-1072.5) pg/mL), then declined at discharge (median (IQR): 764.5 (569.3-986.8) pg/mL) (P<0.001). Meanwhile, the preoperative FGF-23 level (P=0.028), but not FGF-23 level at discharge (P=0.067) was positively correlated with the cumulative MACCE rate. Multivariable Cox’s analyses found that preoperative FGF-23 level could independently predict cumulative MACCE rate (P=0.015, hazards ratio (HR)=2.940). Conclusion: Preoperative FGF-23 level predicts higher MACCE risk in ULMCAD patients undergoing CABG surgery.